Design of Rainwater Harvesting System in University Campus of Benghazi University, Libya - Bentaher لبنى (Journal of Pure & Applied Sciences, 2023)
The city of Benghazi, like other Libyan cities, suffers from the shortage of renewable water sources. Otherwise, it was necessary to think about sources and technologies to inducement for the shortage of the water resources in Libya cities, such as adopting rainwater harvesting systems; This study aims to calculate the amounts of rainwater harvested from the roofs of buildings, roads, and squares of the university campus of Benghazi University using remote sensing and geographic information systems techniques, using of Google Earth and ArcGIS10.5 programs. In addition, studied the extent of the rainwater harvested quantity to coverage the human water consumption at the university campus; According to the study's results, the collected harvested rain water from the roofs of buildings, squares and roads in a year is 314789.58 m3, by three draining lines with a diameter of 200 mm, and slope from 0.002 to 0.009, so that the three lines meet a circular collection tank with a diameter of 27 m and depth of 3 m. At the end of this study, recommend that the administration of the University of Benghazi adopt the water harvesting system at the campus and provide its requirements for implementation, and to exploit the rainwater that It is harvested by creating gardens and lakes to add an aesthetic view of the university campus, also harvesting rainwater from the roofs of campus buildings facilities avoids the accumulation of ponds in it, so the structural elements are protected from moisture and its harmful effect.